The assessment of IL-6 in immune response to hepatitis B among hepatitis B vaccinated individuals in Specialist Hospital Sokoto State, North-Western Nigeria - Abubakar Babangida Usman; Safiyya Muazu; Adamu Muhammad Ibrahim; Sabo Ezra Funom; Andrew Godwin Smoklo; Zulkifilu Umar; Mustapha Umar Kalgo; Kabiru Bello Aliyu; Kabir Magaji Hamid (The Egyptian Journal of Internal Medicine)
Abstract Background Hepatitis B remains a major health burden with perinatal transmission being a key concern in endemic regions in countries like Nigeria. Vaccination is critical but the 5–10% non-response rate necessitates research into biomarkers like IL-6 that may predict immunogenicity. This study assessed hepatitis B vaccine response and the role of IL-6 in vaccinated individuals in Specialist Hospital, Sokoto State, Nigeria. Methods This cross-sectional study quantified IL-6 and hepatitis B surface antibody (HBsAb) levels in 50 vaccinated subjects in Sokoto, Nigeria, using ELISA and chemiluminescence immunoassays. Sociodemographic data including age, gender, and vaccine route were collected via questionnaires. Correlation analysis was performed between IL-6 and HBsAb levels to assess vaccine response prediction potential. Results Among the 50 participants, 84% demonstrated seroprotection based on adequate HBsAb titers, confirming the effectiveness of vaccination programs. However, 16% remained insufficiently immunized despite vaccination, highlighting interindividual variability warranting further investigation. IL-6 levels were predominantly normal (92%) with few (8%) exhibiting low levels, indicating appropriate inflammatory regulation overall. No sociodemographic factors emerged as significant predictors. A non-significant (p = 0.354) negative correlation (r = − 0.134) was found between IL-6 and HBsAb, suggesting IL-6 may not strongly predict hepatitis B vaccine response. Conclusion While protection rates align with WHO benchmarks, non-responders indicate a need to uncover immune and genetic mechanisms influencing vaccine outcomes through larger studies. The negative IL-6/HBsAb correlation warrants further analysis given IL-6’s regulatory role.